2016
DOI: 10.1371/journal.pone.0154906
|View full text |Cite
|
Sign up to set email alerts
|

Damage Control Orthopedics Management as Vital Procedure in Elderly Patients with Femoral Neck Fractures Complicated with Chronic Renal Failure: A Retrospective Cohort Study

Abstract: BackgroundChronic renal failure (CRF) predisposes to hip fractures in elderly patients, with high subsequent mortality. Selection and timing of the surgical procedure of such patients is a serious challenge. Many clinicians believe in earlier surgery as preferable and providing better outcomes. Damage control orthopedics (DCO) aids to adjust and optimize the overall condition of patients.MethodsIn 32 patients with femoral neck fractures complicated with CRF, we evaluated how the timing of the surgery determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…However, in dialysis patients, a delayed operation did not contribute significantly to the mortality rate compared to that in the non-dialysis cohort [29]. The current study found that delaying surgery for a period of time did not negatively impact the incidence of postoperative complications [30].…”
Section: Discussioncontrasting
confidence: 48%
“…However, in dialysis patients, a delayed operation did not contribute significantly to the mortality rate compared to that in the non-dialysis cohort [29]. The current study found that delaying surgery for a period of time did not negatively impact the incidence of postoperative complications [30].…”
Section: Discussioncontrasting
confidence: 48%
“…In previous studies, delaying surgery by more than 48 h in elderly patients with hip fractures led to an increase in post-surgery mortality rates. However, a recent study showed that delaying surgery for several days did not negatively impact the incidence of postoperative adverse events [ 36 ]. As a consequence of the above, it is believed that this lower reduction in preoperative LOS is not a failure of the methodology applied.…”
Section: Resultsmentioning
confidence: 99%
“…Delaying surgery to optimise the patient resulted in decreased mortality in 1 study. 25 Grimsrud et al described a technique of strengthening calcar using a part of the osteotomised neck and a particular wiring technique to prevent later varus collapse. He also used collared long stem.…”
Section: Discussionmentioning
confidence: 99%